Pendampingan Pastoral Terhadap Remaja Pecandu Minuman Keras di Jemaat GMIM Moria Darunu Wilayah Wori Dua - Zala, Marcella Valeria; Kalalo, Jefry (Educatio Christi, 2021)
This article aims to provide Pastoral assistance to teenagers who are alcoholics in the GMIM Moria Darunu Congregation, Wori Dua Region. Adolescence is a transition period from childhood to adulthood. Adolescence is said to be a period of searching for identity because teenagers face difficult and confusing situations. On the one hand they still act like children, but on the other hand they act like adults. The problems in this research study are found in congregational and social life, so it cannot be denied that the behavior of teenagers has been entangled in the habit of drinking alcohol which ultimately has an impact on the physical and mental health of the teenagers themselves. The method used is a qualitative approach with data collection techniques through interviews, observation and document analysis as data collection tools. research results show that alcohol threatens the future of the Church. To anticipate the spread of the habit of drinking alcohol among teenagers, the church needs to provide pastoral assistance for teenagers in order to heal from an attitude of dependence on alcohol. The implications of this research can be useful for the development of pastoral theology for church services. This article was prepared by explaining what Pastoral assistance is, what the function of Pastoral Assistance is, what teenagers are, what alcohol is, and how pastoral assistance is carried out by the Church. This article ends with the author's conclusion.